The Transformation of Documenting and Coding: Evaluation and Management Codes for Outpatient Neurology Services. Issue 6 (December 2021) - Villanueva, Raissa; Busis, Neil A.; Cohen, Bruce H.; Ciccarelli, Luana
ABSTRACT: This article discusses the optimal ways to document and code for outpatient evaluation and management (E/M) codes. Since the changes for Current Procedural Terminology ( CPT ) codes 99202-99215 were finalized for 2021, they have been modified by the Centers for Medicare & Medicaid Services (CMS) in their Medicare Physician Fee Schedule and by technical corrections issued on March 9, 2021. The 21st Century Cures Act mandated that patients can access their notes and test results immediately. These developments have transformed medical documentation and coding for outpatient E/M services. One year in, the authors have a better understanding of the subtleties of documenting and accurately determining levels of service for outpatient encounters using these new rules and regulations, and they share key insights gained by experience with the new system.